Beyond the Wall: Exopolysaccharides in the Biofilm Lifestyle of Pathogenic and Beneficial Plant-Associated Pseudomonas - Zaira Heredia-Ponce; Antonio de Vicente; Francisco M. Cazorla; José Antonio Gutiérrez-Barranquero (Microorganisms, 2021)
The formation of biofilms results from a multicellular mode of growth, in which bacteria remain enwrapped by an extracellular matrix of their own production. Many different bacteria form biofilms, but among the most studied species are those that belong to the Pseudomonas genus due to the metabolic versatility, ubiquity, and ecological significance of members of this group of microorganisms. Within the Pseudomonas genus, biofilm studies have mainly focused on the opportunistic human pathogen Pseudomonas aeruginosa due to its clinical importance. The extracellular matrix of P. aeruginosa is mainly composed of exopolysaccharides, which have been shown to be important for the biofilm architecture and pathogenic features of this bacterium. Notably, some of the exopolysaccharides recurrently used by P. aeruginosa during biofilm formation, such as the alginate and polysaccharide synthesis loci (Psl) polysaccharides, are also used by pathogenic and beneficial plant-associated Pseudomonas during their interaction with plants. Interestingly, their functions are multifaceted and seem to be highly dependent on the bacterial lifestyle and genetic context of production. This paper reviews the functions and significance of the exopolysaccharides produced by plant-associated Pseudomonas, particularly the alginate, Psl, and cellulose polysaccharides, focusing on their equivalents produced in P. aeruginosa within the context of pathogenic and beneficial interactions.